Inflammatory biomarkers in patients in Simvastatin treatment: No effect of co-enzyme Q10 supplementation. (January 2019) - Hansen, Maria; Kuhlman, Anja C.B.; Sahl, Ronni E.; Kelly, Bo; Morville, Thomas; Dohlmann, Tine L.; Chrøis, Karoline M.; Larsen, Steen; Helge, Jørn W.; Dela, Flemming
Abstract: Purpose: Atherosclerosis is a major risk factor for cardiovascular disease (CVD) and is known to be an inflammatory process. Statin therapy decreases both cholesterol and inflammation and is used in primary and secondary prevention of CVD. However, a statin induced decrease of plasma concentrations of the antioxidant coenzyme Q10 (CoQ10), may prevent the patients from reaching their optimal anti-inflammatory potential. Here, we studied the anti-inflammatory effect of Simvastatin therapy and CoQ10 supplementation. Methods: 35 patients in primary prevention with Simvastatin (40 mg/day) were randomized to receive oral CoQ10 supplementation (400 mg/d) or placebo for 8 weeks. 20 patients with hypercholesterolemia who received no cholesterol-lowering treatment was a control group. Plasma concentrations of lipids and inflammatory biomarkers (interleukin-6 (IL6); -8 (IL8); -10 (IL10), tumor necrosis factor-α (TNFα); high-sensitivity C reactive protein (hsCRP)) as well as glycated hemoglobin (HbA1c) were quantified before and after the intervention. Results: No significant change in inflammatory markers or lipids was observed after CoQ10 supplementation Patients in Simvastatin therapy had significantly (P < 0.05) lower baseline concentration of IL6 (0.31 ± 0.03 pg/ml), IL8 (1.6 ± 0.1 pg/ml) IL10 (0.16 ± 0.02 pg/ml) and borderline (P = 0.053) lower TNFα (0.88 ± 0.05 pg/ml), but not hsCRP (1.34 ± 0.19 mg/l) compared with the control group (0.62 ± 0.08, 2.6 ± 0.2, 0.25 ± 0.01, 1.07 ± 0.09, and 1.90 ± 0.35, respectively). Conclusions: Simvastatin therapy has beneficial effects on inflammatory markers in plasma, but CoQ10 supplementation seems to have no additional potentiating effect in patients in primary prevention. In contrast, glucose homeostasis may improve with CoQ10 supplementation.